2019
DOI: 10.3390/w11102156
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Chlorine Damage Using Enhanced Green Fluorescent Protein-Expressing Escherichia coli

Abstract: This study investigated how chlorine inactivates and damages Escherichia coli cells. E. coli that had transformed to express enhanced green fluorescent protein (EGFP) at the cytoplasm was treated with chlorine. Damage to the cell membrane and cell wall was analyzed by measuring the fluorescence intensity of the leaked EGFP, then accounting for the fluorescence deterioration. At pH 7, E. coli was lethally damaged after treatment with chlorine, but significant leakage of EGFP was not observed. In contrast, signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…(Figure b). Pathogen inactivation by chlorine disinfectant instantly reacts on multiple cellular target sites to disrupt microbial metabolism . Characteristics such as induction of specific genes after chlorination (e.g., DNA repair, oxidative stress, and cell wall repair genes) and high presence of CRB can induce biofilm formation and support the chlorine resistance. The thick hydrophobic cell wall with coating polymeric substances such as mycolic acid in Mycobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…(Figure b). Pathogen inactivation by chlorine disinfectant instantly reacts on multiple cellular target sites to disrupt microbial metabolism . Characteristics such as induction of specific genes after chlorination (e.g., DNA repair, oxidative stress, and cell wall repair genes) and high presence of CRB can induce biofilm formation and support the chlorine resistance. The thick hydrophobic cell wall with coating polymeric substances such as mycolic acid in Mycobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Hypochlorous acid has a destructive and non-selective oxidative effect, while hypochlorite ions inactivate bacteria by damaging the cell wall (15,29). Sodium hypochlorite solutions tend to decompose over time, and decomposition is promoted by heat, light, metal ions, water hardness, low pH and presence of soil (4).…”
Section: Effectives Of Paa Versus Chlorine-based Compoundsmentioning
confidence: 99%
“…Several studies have shown that free chlorine inactivates E . coli without damaging its cell membranes [ 49 52 ] further indicating that the use of PMAqPCR is not appropriate to determine the capacity of chlorine to kill bacteria.…”
Section: Discussionmentioning
confidence: 99%